The Artistic Heritage of Spanish Writers of the First Half of the 20th Century (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Each text and each movement has its own style. Literary type is a product of written speech that does not have elements characteristic of poetry, such as weight and rhyme. Prose as a form of written speech appeared later than poetry, as in the literature of European nations, as well as in the literature of Eastern nations. If the prose speech was quiet and lofty, like the poetic speech, when it first appeared, by the first quarter of the 20th century, it began to be devoid of excess luxury, and it increasingly obeyed the rules of realistic imagery. Artistic simplicity, naturalness, tendency to approach real life became the main criteria of Nasr. At the same time, writers did not forget that prose is a form of artistic speech. Based on their own creative style and the nature of the work being written, they chose the necessary rhythm (tone) and effectively used and are using image tools.